1997
DOI: 10.1099/00221287-143-4-1381
|View full text |Cite
|
Sign up to set email alerts
|

The soybean cultivar specificity gene noIX is present, expressed in a nodD-dependent manner, and of symbiotic significance in cultivar-nonspecific strains of Rhizobium (Sinorhizobium) fredii

Abstract: Rhizobium (now Sinorhizobium) fredii is a symbiotic nitrogen-fixing bacterium that can nodulate soybean in a cultivar-specific manner. This process is governed by a set of negatively acting nodulation genes termed nolXWBTUV. These genes prevent R. fredii strain USDA257 from infecting soybean cultivars such as McCall, but they do not block nodulation of cultivar Peking. R. fredii strain USDA191 contains DNA sequences that hybridize to nolXWBTUV, yet it forms normal nitrogen-fixing nodules on both McCall and Pek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
0
36
1
1
Order By: Relevance
“…NGR234 abolishes Nops secretion and affects the symbiosis in a hostdependent manner . A similar phenotype has been reported in mutant strains of S. fredii USDA257 and HH103 that contain a non-functional secretion machinery (Bellato et al, 1997;de Lyra et al, 2006;Meinhardt et al, 1993).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…NGR234 abolishes Nops secretion and affects the symbiosis in a hostdependent manner . A similar phenotype has been reported in mutant strains of S. fredii USDA257 and HH103 that contain a non-functional secretion machinery (Bellato et al, 1997;de Lyra et al, 2006;Meinhardt et al, 1993).…”
Section: Introductionmentioning
confidence: 51%
“…The presence of multiple copies of the nodD2 gene in S. fredii USDA257 makes Nops secretion constitutive (Bellato et al, 1997;Krishnan et al, 1995). However, in Rhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…This region was designated the soybean cultivar specificity locus. Paradoxically, the same locus was also found in USDA191 (4).…”
mentioning
confidence: 70%
“…On soybean, NolX acts as the determinant of cultivar specificity, preventing S. fredii USDA257 from forming nitrogen-fixing nodules on cultivar McCall soybeans (2,21). Transmission electron microscopy studies have shown that cultivar McCall soybean roots inoculated with S. fredii USDA257 form a few aberrant infection threads, but the bacteria are not released into the host cytosol (4).…”
Section: Discussionmentioning
confidence: 99%
“…S. fredii USDA257 is able to attach and penetrate cultivar McCall roots, but the infection process is aborted prior to the formation of infection threads (4). The inability of S. fredii USDA257 to nodulate cultivar McCall and other advanced soybean cultivars is regulated by a complex genetic locus, nolXWBTUV (2,21). Inactivation of any of the genes in this locus allows the mutant to form nitrogen-fixing nodules on soybean cultivar McCall, indicating a functional role for this locus in soybean cultivar specificity.…”
mentioning
confidence: 99%